2016
DOI: 10.1080/0309877x.2016.1159288
|View full text |Cite
|
Sign up to set email alerts
|

First-year undergraduate induction: Who attends and how important is induction for first year attainment?

Abstract: The first year of study in higher education is a time of major transition for students. While the importance of induction has been widely demonstrated, there is evidence to suggest that not all students benefit equally from participation in induction. This study examined attendance rates at induction, the relationship between induction attendance and first-year attainment and, finally, whether this relationship differed as a function of demographic factors, entry qualifications and the number of credits attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous work (e.g. Murtagh et al 2016;Reay et al 2002;Richardson 2012;Ridley 2007) has reported lower attainment from BAME students relative to their non-BAME peers. We observed the same pattern of results.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous work (e.g. Murtagh et al 2016;Reay et al 2002;Richardson 2012;Ridley 2007) has reported lower attainment from BAME students relative to their non-BAME peers. We observed the same pattern of results.…”
mentioning
confidence: 89%
“…Unfortunately, one notable feature of many higher education systems is that students from some backgrounds do not achieve the same academic attainments as do others. In the UK, at risk demographics include older students, those from lower social economic status (SES) backgrounds and members of some ethnic minorities (Broeke and Nicholls 2007;Jetten et al 2008;Labi 2015;Mok et al 2016Mok et al , 2017Murtagh et al 2016;Reay et al 2002;Richardson 2012;Ridley 2007;Woolf et al 2013) and there is also some evidence that lower attainment in Black, Asian or Minority Ethnic (BAME) students compared to white students is greater when they are part-time, older, and female (Richardson 2008). Similar attainment gaps have been observed in other areas of the world, such as wider Europe and the US (see Heath et al 2008;Schnell and Azzolini 2015;Stevenson and Whelan 2013, but cf.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if students are actively supported during their transition to university they are more likely to develop the skills required to progress successfully to the second year of their programme (Thomas 2012;Thomas et al 2017;Pennington et al 2018). Additionally, research conducted by Murtagh et al (2017) indicates the importance of attendance at induction to students first year attainment.…”
Section: Why Do Students Withdraw?mentioning
confidence: 99%
“…In addition to the academic and social readiness activities discussed above, a physical orientation of the university campus is beneficial to new students (Yorke andLongden 2004, Cook, Rushton, McCormick andSouthall 2005). Further, research conducted by Murtagh et al (2017) indicates the importance of attendance at induction to students' first year attainment. Induction by Design Drawing on the student success literature discussed above, a new induction by design on-entry approach was developed at the private higher education institution.…”
Section: Induction By Designmentioning
confidence: 99%
“…There is evidence in the literature which suggested to LLSS staff that it would be beneficial to adopt a new approach to Welcome activities. Murtagh, Ridley,Frings and Kerr-Pertic (2017) argue that student attendance in induction events has been found to correlate with academic outcomes; thus, improving induction can increase student attendance and engagement. This is a key area of interest for higher education (HE) professionals concerned with student retention and success.…”
Section: Literature Reviewmentioning
confidence: 99%